STRATEGI PENGEMBANGAN AIR TERJUN OEHALA SEBAGAI DAYA TARIK EKOWISATA BERBASIS MASYARAKAT DI KABUPATEN TIMOR TENGAH SELATAN, NUSA TENGGARA TIMUR - Sanam, Syul Rosli (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2019)
Oehala Waterfall is one of the tourism potentials which has been decided as one of the natural tourist attraction at Timor Tengah Selatan regency. The development is not able to meet the expectation which is only to supply the tourism facilities at Oehala Waterfall location. In the ecotourism context, the development should be oriented to strengthen then the local community role and involvement. However, in the development of Oehala tourist attraction, the local community has not been involved actively because of the weakness of the human resources in tourism aspect. The objective of this research are: 1) Analizing the internal environment condition and Oehala tourist attraction external; and 2) Formulating the community based tourism ecotourism development program at Oehala Waterfall tourist attraction. The result of the research shows that in successing the community based ecotourism development at Oehala tourist attraction, so the strategy and program which should be developed are the product development and the natural tourist attraction and ecotourism culture based, the development of tourism facility, the development of human resources and organization establishment, the development of promotion and marketing, and also the ecotourism development which is eco-friendly.